ON THE POSSIBILITY OF GOAT'S MILK AND ADAPTED GOAT MILK FORMULAS USAGE IN CHILDREN FEEDING - T. E. Borovik; N. N. Semenova; O. L. Lukoyanova; N. G. Zvonkova; V. A. Skvortsova; I. N. Zakharova; T. N. Stepanova ("Paediatrician" Publishers LLC, 2013)
The data on goat's milk composition, its physical and chemical as well as immunological characteristics in comparison with cow and breast milk are shown in this article. The authors discuss beneficial properties of the goat's milk and goat milk formulas and the experience of their usage in healthy and ill infants as an alternative of the cow's milk. The assessment of the modern adapted and differentiated according to the age groups goat milk formulas for infants is represented in the study.